Production Risk Analysis in Maize: Comparative Insights from Major Producing Countries - Aminda, Fadilla Ristya; Dhamira, Aura; Sari, Ayu Kumala (West Science Interdisciplinary Studies, 2025)
Increasing maize productivity is a strategic step for developing the global agricultural sector. Maize plays an important role as a source of food, feed, industrial raw materials, and energy sources. However, maize production faces internal risks, such as capital availability, management capacity, land ownership, and external risks, such as climate change, pest attacks, and limited agricultural inputs. This study discusses the development of maize production risks in ten major producing countries, including the USA, China, Brazil, Argentina, and Mexico. The study uses secondary data from FAOSTAT from 1961-2021 (61 years). The study uses a qualitative method by analysing maize production trends and risks using the coefficient of variation (CV) analysis. The analysis results show that the USA ranks first as the largest maize producer in the world, followed by China and Brazil, with an increasing trend over the past 61 years. This is related to adopting biotechnology, food production, and precision farming systems. France and the USA have low CV values of 0.36 and 0.40, indicating that the risk of maize production in the two countries is relatively low compared to the other eight countries. Maize stabilization in the USA is supported by implementing irrigation and precision farming models to reduce the impact of drought due to climate variability. On the other hand, Argentina, Ukraine, and Indonesia have high CV values, indicating a high risk of maize production in the three countries. Several factors causing high production risks are climate change in the form of increasing average annual temperatures, attacks of Maize Stunt Disease, political challenges, inaccurate use of fertilizers, low technology adoption, and limited resources.